First-Attempt Success Between Anatomically and Physiologically Difficult Airways in the National Emergency Airway Registry - Nikolla, Dhimitri A.; Offenbacher, Joseph; Smith, Silas W.; Genes, Nicholas G.; Herrera, Osmin A.; Carlson, Jestin N.; Brown, Calvin A. (Anesthesia and analgesia, 2024)
BACKGROUND: In the emergency department (ED), certain anatomical and physiological airway characteristics may predispose patients to tracheal intubation complications and poor outcomes. We hypothesized that both anatomically difficult airways (ADAs) and physiologically difficult airways (PDAs) would have lower first-attempt success than airways with neither in a cohort of ED intubations. METHODS: We performed a retrospective, observational study using the National Emergency Airway Registry (NEAR) to examine the association between anticipated difficult airways (ADA, PDA, and combined ADA and PDA) vs those without difficult airway findings (neither ADA nor PDA) with first-attempt success. We included adult (age ≥14 years) ED intubations performed with sedation and paralysis from January 1, 2016 to December 31, 2018 using either direct or video laryngoscopy. We excluded patients in cardiac arrest. The primary outcome was first-attempt success, while secondary outcomes included first-attempt success without adverse events, peri-intubation cardiac arrest, and the total number of airway attempts. Mixed-effects models were used to obtain adjusted estimates and confidence intervals (CIs) for each outcome. Fixed effects included the presence of a difficult airway type (independent variable) and covariates including laryngoscopy device type, intubator postgraduate year, trauma indication, and patient age as well as the site as a random effect. Multiplicative interaction between ADAs and PDAs was assessed using the likelihood ratio (LR) test. RESULTS: Of the 19,071 subjects intubated during the study period, 13,938 were included in the study. Compared to those without difficult airway findings (neither ADA nor PDA), the adjusted odds ratios (aORs) for first-attempt success were 0.53 (95% CI, 0.40-0.68) for ADAs alone, 0.96 (0.68-1.36) for PDAs alone, and 0.44 (0.34-0.56) for both. The aORs for first-attempt success without adverse events were 0.72 (95% CI, 0.59-0.89) for ADAs alone, 0.79 (0.62-1.01) for PDAs alone, and 0.44 (0.37-0.54) for both. There was no evidence that the interaction between ADAs and PDAs for first-attempt success with or without adverse events was different from additive (ie, not synergistic/multiplicative or antagonistic). CONCLUSIONS: Compared to no difficult airway characteristics, ADAs were inversely associated with first-attempt success, while PDAs were not. Both ADAs and PDAs, as well as their interaction, were inversely associated with first-attempt success without adverse events.